Topological analysis of hydrogen oxidation reaction kinetics at Ni/YSZ anode of the solid oxide fuel cell - Dar, Yasir Rasool (Curtin University, 2011)
The understanding of the mechanisms and kinetics of reactions that occur on the electrodes hold the key to further advances in solid oxide fuel cell (SOFC) technology. The typical material widely used as anode in SOFC is Nickel/Yttria-stabilised Zirconia (Ni/YSZ). The kinetics of the hydrogen oxidation reaction mechanism at Ni/YSZ anode of the SOFC is investigated in this work using the reaction route (RR) graph method, which is a relatively new graphical method for the analysis of reaction kinetics based on the electrical analogy.A mechanism for the hydrogen oxidation reaction consisting of the most promising elementary steps is chosen for the analysis. The RR graph for this mechanism is constructed using the standard procedures. The graph is reduced by exploiting its analogy with electrical resistive circuits. Making use of this reduced graph, an analytical expression for the overall reaction rate is derived for the first time. This rate expression was found to approximate the overall rate obtained using the conventional quasi steady state (QSS) methodology satisfactorily. The reaction pathway containing the two hydrogen spill-over reactions is identified as the dominant pathway in the mechanism. Further analysis reveals that the hydrogen spill-over to oxide ion is the slowest reaction step with highest step resistance and governs the rate of the over-all reaction.